Experimental Study on Performance of Plume Abatement and Water-saving Cooling Tower with Condensate Method - Mingxiao JIA; Sanji HU; Hao LI; Bin WANG (Zhongguo dianli)
The condensate cooling towers for plume abatement and water-saving have been installed and applied in China in the recent years. To assess its plume abatement and water-saving performance, related experimental studies were conducted on a cooling tower with designed circulating water rate of 4 000 m3/h, where the outlet air parameters and water saving rate of this cooling tower were tested. When the circulation water volume was close to the design value, the outlet air dry-wet bulb temperature and velocity distribution were presented with the winter plume abatement mode turned on. The testing result shows that at the exit of the condensate cooling tower, the air flow velocity is higher around the wall surface than at the tower center. The average weighted air relative humidity was 64.2% such that no visible plume will form since the outlet air plume dilution line always lies in the unsaturated region. The amount of condensate water recollected was 11.357 m3/h and the mass of water loss was 45.440 m3/h due to evaporation. The water-saving rate of this cooling tower was 25% under testing conditions. The results can provide beneficial reference for the performance research of plume abatement and water-saving cooling towers.